Case report: tricuspid valve myxoma: an uncommon presentation of a common tumor - Abdul Wajid Khan Faisal; Waseem Riaz; Tahir Naveed; Muhammad Hassan Iqbal; Asif Hassan; Syed Asif Ali (Journal of the Pakistan Medical Association, 2021)
Amongst the benign cardiac tumors atrial Myxomas are commonest. Tricuspid valve attachment is an uncommon site for cardiac Myxoma. We present a case of an 18 years old girl who presented to us with history of shortness of breath, abdominal distension, leg swelling, palpitations and dizziness for two months. On Echocardiography there was a large pedunculated mass attached to tricuspid valve. She underwent surgical excision of the mass. Biopsy confirmed the Myxoma. In conclusion, Myxoma originating from tricuspid valve are rare tumours which can cause tricuspid valve obstruction and right heart failure symptoms due to their location. In these cases shortness of breath, embolisation and symptoms of venous congestion are commonly observed. Key Words: Case report, Myxoma, right heart, cardiac CT, tricuspid valve. Continuous...